PENGARUH BUKU SAKU TERHADAP TINGKAT KECUKUPAN GIZI PADA REMAJA (Studi Di SMA Teuku Umar Semarang Tahun 2016) - Maharani Widya Purnama sari; Sri Achadi Nugraheni; Ronny Aruben (Jurnal Kesehatan Masyarakat (Undip), 2017)
Nutrition education through the pocketbook is one solution to convert knowledge of nutrition and nutritional adequacy levels in adolescents. The purpose of this study was to analyze the differences in nutrition knowledge and nutritional adequacy levels before and after nutrition education between the two groups. The study design quasy experiment with the design of non-randomized control group pretest-posttest design. The sample was 70 subjects (35 treatment group and 35 control group) with a purposive sampling techniques. Before being given booklets, each group was given exposure on the prevention of malnutrition and measurement of knowledge and level of initial nutritional adequacy. In the treatment group was given a pocket book and quiz whereas the control group did not. After that, each group performed measurements of knowledge and level of nutritional adequacy of the final. In this study using the paired t test, Wilcoxon signed rank test, Mann Whitney test, and independent t test. The results showed the treatment group increased nutritional knowledge level of 39.6%, while the control group decreased nutritional knowledge level of 17.1%. The treatment group decreased energy sufficiency level of 5.7%; protein sufficiency rate increased by 5.7%; sufficient levels of fat decreased by 5.7%. The control group increased energy sufficiency level of 5.7%; protein sufficiency rate increased by 5.9%; fat sufficiency level increased by 34.3%. There is a difference of knowledge between the two groups (p = 0.001). There is a difference in energy sufficiency level (p = 0.019), protein (p = 0.002), and fat (p = 0.001) between the two groups. It is concluded that there are differences in knowledge of nutrition and nutritional adequacy level (energy, protein, fat) between the two groups (p <0.05).